Accelerated synthesis of novel 1,2,4-triazolo[3,4-b][1,3,4]-thiadiazepines under microwave irradiation - Cetin, Ahmet (Japan Inst Heterocyclic Chemistry, 2006)
A convenient and efficient one step, base catalyzed synthesis of 3,5disubstituted-4-amino-1,2,4-triazoles by condensation of thiol and hydrazide is presented. An environmentally benign and economic synthesis for the title compounds is described from readily accessible substituted 4-amino-5-mercapto1,2,4-triazoles and substituted chalcones on basic alumina that are accelerated by exposure to microwave irradiation.
Keywords: Solid Support Synthesis; Media